A study on the technological pedagogical contextual knowledge of science teacher candidates across different years of study - Cirit, Didem Karakaya; Canpolat, Erdal (Springer, 2019)
This case study survey investigates the Technological Pedagogical Contextual Knowledge (TPCK) of Science Teacher Candidates (STC) across different years of study in the Topic of Renewable Energy (TRE). In line with the transformative model, the study treats TRE-TPCK as a new knowledge domain emerging from the interaction between content, technology, pedagogy and contextual knowledge. Participants were 36 Science Education students who were in their 1st, 2nd, 3rd and 4th years of study during the 2014-2015 academic year. Teacher candidates' TPCK was identified through semi-structured interviews based on (1) Vignettes, (2) Anecdotes from a teacher named Zeynep and the (3) Content Presentation Technique (CPT). The data were analyzed by using the content analysis technique. The findings showed that the TRE-TPCK of teacher candidates across different years of study was at a similar and less-than-ideal level. STCs in different years of study mostly disregarded the macro and meso contexts when teaching the topic of renewable energy and were partially competent in the sub-meso, micro and sub-micro contexts. They particularly lacked technology-integrated evaluation knowledge when teaching TRE.
Keywords: Contextual knowledge; Renewable energy; TPCK; Teacher candidate; Vignette